PENGETAHUAN PEROKOK AKTIF TENTANG QANUN KAWASAN TANPA ROKOK DENGAN MOTIVASI BERHENTI MEROKOK PADA MAHASISWA - Marthunis Marthunis; Teuku Tahlil (Jurnal Ilmiah Mahasiswa Fakultas Keperawatan, 2019)
Smoking is a behavior that is still practiced by many people, including students, even though the danger of smoking is often conveyed in the mass/electronic media and the government has issued a Qanun on non-smoking areas. Motivation is a process that trigger an individual's intensity, direction, and perseverance to stop smoking. The purpose of this study was to examine the relationship between the knowledge about Qanun Number 5 of 2016 (KTR) with motivation to quit smoking of students in Syiah Kuala University Banda Aceh. This study used a cross sectional design with a sample of 110 students selected by purposive sampling technique. Data collection was conducted using a questionnaire that was analyzed by chisquare test. The results of this study stated that the level of student knowledge about Qanun Number 5 Year 2016 (KTR) at the Syiah Kuala University in Banda Aceh was in the unfavorable category (51.8%), the level of motivation to quit smoking for students at the Syiah Kuala Banda Aceh University was in the category low (52.7%), and there was a relationship between the level of knowledge about Qanun Number 5 of 2016 (KTR) with motivation to quit smoking in Syiah Kuala University students (p-value = 0,000). Therefore, it is recommended that te university not only to create a No-Smoking Zone, but also to continue to monitor and evaluate to see the extent of the implementation of the No-Smoking Zone and to increase te awareness of students in order to disseminate information about the No-Smoking Zone.